Atomic Spectrometry Update – a review of advances in environmental analysis. Issue 1 (2nd November 2018) - Bacon, Jeffrey R.; Butler, Owen T.; Cairns, Warren R. L.; Cook, Jennifer M.; Mertz-Kraus, Regina; Tyson, Julian. F.
Abstract : This review covers advances in the analysis of air, water, plants, soils and geological materials by a range of atomic spectrometric techniques including atomic emission, absorption, fluorescence and mass spectrometry. Abstract : This is the 34 th annual review of the application of atomic spectrometry to the chemical analysis of environmental samples. This Update refers to papers published approximately between August 2017 and June 2018 and continues the series of Atomic Spectrometry Updates (ASUs) in Environmental Analysis 1 that should be read in conjunction with other related ASUs in the series, namely: clinical and biological materials, foods and beverages; 2 advances in atomic spectrometry and related techniques; 3 elemental speciation; 4 X-ray spectrometry; 5 and metals, chemicals and functional materials. 6 The review is not intended to be a comprehensive overview but selective with the aim of providing a critical insight into developments in instrumentation, methodologies and data handling that represent a significant advance in the use of atomic spectrometry in the environmental sciences.